Modeling bias and energy use realities in Mediterranean housing - Vardopoulos, Ioannis; Vassiliades, Constantinos; Kalogirou, Soteris A.; Santamouris, Mattheos (My University, 2026)
The imperative for energy-efficient buildings has never been more pronounced, particularly in regions where outdated infrastructure continues to undermine sustainability efforts. This chapter scrutinizes the precision of energy certification models. Despite their widespread use in certifying energy performance, their predictive reliability remains an open question. Through a comparative analysis of real-world energy consumption versus simulated estimates across common residential typologies, this research unveils critical discrepancies that call into question the accuracy of existing methodologies. Findings reveal that while heating load predictions align moderately well with actual usage, cooling and lighting consumption estimates exhibit substantial inaccuracies, raising concerns about the tool’s ability to account for climate-specific conditions and occupant behaviour, bearing broader implications. This work, indeed, serves as a clarion call for policymakers, industry professionals, and sustainability advocates to re-evaluate the efficacy of current regulatory frameworks. If energy performance certification is to fulfil its role as a driver of meaningful efficiency improvements, it must evolve beyond static models to embrace a more nuanced, data-driven approach. This work lays the groundwork for a new era in building energy evaluation – one that is rigorous, reflective of real-world conditions, and genuinely instrumental in shaping sustainable urban futures.
Keywords: Building Energy Efficiency; Energy utilization; Energy performance; Housing